Ecology in the eyes of non-ecologist - Uchmański, Janusz (Studia Ecologiae et Bioethicae, 2017)
Ecology is a part of biology which deals with the life of plants and animals in their environment. Nature protection is a practical activity in which ecology is applied. Ecology is the most biological part of biology because it deals with individuals in their environment and individuals exist only in biology. The most important problem of ecology is biological diversity: its changes and persistence. Ecologists always focus their investigations on some ecological systems. In the classical approach, the most important mechanisms explaining the functioning of ecological systems are dependences on the densities of individuals in populations. Mathematical models usually applied in ecology are difference and differential equations, which is in accordance with the assumption about density-dependence but focuses ecologists' interests on the stability of ecological systems. Evolutionary biology and ecology domains overlap only partly. Evolutionary ecology is dealing with individuals with optimal features, while ecology considers also losers of natural selection. The mathematical method used in classical ecology were taken from physics. It raises the question: are they proper for ecology. Recently, the so-called individual-based approach emerged, which stresses that in order to understand the diversity of nature one has to go back directly to individuals as basic “atoms”, from which ecological systems consist, and not to concentrate on densities. Such an approach gives a very complicated picture of ecological systems dynamics. An alternative way of describing ecological systems dynamics exists however in ecology, namely by means of matter cycling and energy flows. It allows using difference and differential equations during model building and was approved many times in practical applications.